2007
DOI: 10.1194/jlr.m600050-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of phytol to phytanic acid in the mouse, and the role of PPARα in its regulation

Abstract: Phytol, a branched-chain fatty alcohol, is the naturally occurring precursor of phytanic and pristanic acid, branched-chain fatty acids that are both ligands for the nuclear hormone receptor peroxisome proliferator-activated receptor a (PPARa). To investigate the metabolism of phytol and the role of PPARa in its regulation, wild-type and PPARa knockout (PPARa 2/2 ) mice were fed a phytolenriched diet or, for comparison, a diet enriched with Wy-14,643, a synthetic PPARa agonist. After the phytolenriched diet, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…In the liver of PPAR␣-null mice, the basal expression levels of FALDH were low, about a fifth to a tenth of that in the corresponding tissue of wild-type mice, and a small but significant induction by sesame was observed. These results indicated that the induction of FALDH expression by sesame is dependent on the expression of PPAR␣, which is consistent with a recent publication (16). The sesame seeds may contain a natural ligand for PPAR␣ (3).…”
Section: Faldh Was Induced In the Liver Of Normal Mice Fed Sesame Butsupporting
confidence: 92%
See 1 more Smart Citation
“…In the liver of PPAR␣-null mice, the basal expression levels of FALDH were low, about a fifth to a tenth of that in the corresponding tissue of wild-type mice, and a small but significant induction by sesame was observed. These results indicated that the induction of FALDH expression by sesame is dependent on the expression of PPAR␣, which is consistent with a recent publication (16). The sesame seeds may contain a natural ligand for PPAR␣ (3).…”
Section: Faldh Was Induced In the Liver Of Normal Mice Fed Sesame Butsupporting
confidence: 92%
“…The expression of all the mRNAs was largely induced in mouse liver upon administration of a PPAR␣ agonist. Gloerich et al (16) recently found that the conversion of phytol to phytanic acid is regulated via PPAR␣ using null mice. The present observations support their conclusion.…”
Section: Faldh Was Induced In the Liver Of Normal Mice Fed Sesame Butmentioning
confidence: 99%
“…We wished to know whether GGOH is oxidized to GGA in human cells, because GGA has been shown to be a biologically active compound that can induce cell death in human hepatoma cells (16). In the literature, enzymatic conversion of phytol to phytanic acid has been highly scrutinized to explore pathogenesis of Refsum disease (4,15,23). Phytol and dihydrophytol are oxidized to phytenal and phytanal, respectively, by mitochondrial alcohol dehydrogenase; both aldehydes are further oxidized to phytenoic acid and phytanic acid by mitochondrial/ microsomal fatty aldehyde dehydrogenase.…”
Section: Preparation Of Lipid Extracts From Huh-7 Cellsmentioning
confidence: 99%
“…A previous study showed that phytanic acid had cytotoxic effects on the mitochondria and stellate cells in the rat brain (Schönfeld et al, 2006). However, both phytanic and pristane acids play a regulatory role in adipocyte differentiation and polyester, glucose, and lipid metabolism (Heim, 2002); it can promote fatty acid b-oxidation and significantly lower liver triglyceride and plasma fatty acids (Gloerich et al, 2007). In this study, both commercial pellet feed-feeding and small trash fish-feeding crabs contained high levels of phytanic acid, suggesting that crab is similar to other high phytanic acid foods and may have potential health functions.…”
Section: Phytanic Acidmentioning
confidence: 99%